Time optimal control of mini-submarine missile based on control variable parameterization with enhanced time-scaling method - Nuan Wen; Zhenghua Liu; Le Chang; Yan Ren (2016 IEEE Chinese Guidance, Navigation and Control Conference (CGNCC), 2016)
This paper provides systematic analysis and design procedure for the time optimal control of a certain mini-submarine missile. Nowadays, horizontal launch with vertical separation proves to be one of the key technologies of the submarine-to-air missile. Control variable parameterization (CVP), as an optimal strategy, will be adopted to yield a prospective result. Particularly, to achieve fastest vertically, the essential problem remains to be a Bang-Bang control issue. Then the enhanced time-scaling transformation turns out to be an appropriate solution. Two controllers, that is, the proportional-derivative controller and the adopted CVP optimal controller are compared by conducting experiments in mathematical simulation.